Effect of Opioid on Adult Hippocampal Neurogenesis - Yue Zhang; Horace H. Loh; Ping-Yee Law (The Scientific World Journal)
During the past decade, the study of the mechanisms and functional implications of adult neurogenesis has significantly progressed. Many studies focus on the factors that regulate proliferation and fate determination of adult neural stem/progenitor cells, including addictive drugs such as opioid. Here, we review the most recent works on opiate drugs’ effect on different developmental stages of adult hippocampal neurogenesis, as well as the possible underlying mechanisms. We conclude that opiate drugs in general cause a loss of newly born neural progenitors in the subgranular zone of dentate gyrus, by either modulating proliferation or interfering with differentiation and maturation. We also discuss the consequent impact of regulation of adult neurogenesis in animal’s opioid addiction behavior. We further look into the future directions in studying the convergence between the adult neurogenesis field and opioid addiction field, since the adult-born granular cells were shown to play a role in neuroplasticity and may help to reduce the vulnerability to drug craving and relapse.